2019
DOI: 10.3390/en12163062
|View full text |Cite
|
Sign up to set email alerts
|

Techno-Economic Analysis of a Residential PV-Storage Model in a Distribution Network

Abstract: The high penetration level of photovoltaic (PV) generation in distribution networks not only brings benefits like carbon savings, but also induces undesirable outcomes, like more harmonic components and voltage fluctuations. Driven by decreasing costs of energy storage, the focus of this paper is to investigate the feasibility of applying energy storage in the grid-connected PV system to mitigate its intermittency. Firstly, to appreciate the functionality of storage, a generic PV-battery-supercapacitor model w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…SOC max ≥ SOC t ≥ SOC min (16) where SOC t , SOC t−1 denotes state of charge at time t and t − 1, respectively; P SCM is the power output/input of SCM; η SCM is the SCM efficiency; m is the number of SCM; C SCM is the nominal capacity; and V SCM is the ultra-supercapacitor nominal voltage. The last term in this equation represents the self-discharge phenomenon η sd .…”
Section: Energy Self-consumption (E Sc ) and Energy Self-sufficiency (E Ss )mentioning
confidence: 99%
See 1 more Smart Citation
“…SOC max ≥ SOC t ≥ SOC min (16) where SOC t , SOC t−1 denotes state of charge at time t and t − 1, respectively; P SCM is the power output/input of SCM; η SCM is the SCM efficiency; m is the number of SCM; C SCM is the nominal capacity; and V SCM is the ultra-supercapacitor nominal voltage. The last term in this equation represents the self-discharge phenomenon η sd .…”
Section: Energy Self-consumption (E Sc ) and Energy Self-sufficiency (E Ss )mentioning
confidence: 99%
“…The advantage of the demonstrated solution has been confirmed through the results of the literature. Xiong and Nour [16] show that the high integration level of photovoltaic generation in the grid system brings direct benefits, such as fuel savings and reduction of pollution, but generates undesirable results, such as high harmonic components and fluctuations in power and voltage. The usage of large SCM units at the domestic level is limited due to its high investment costs.…”
Section: Introductionmentioning
confidence: 99%
“…Those works found the optimal (1) sizing of PV systems and (2) the capacity of the ESS in solving the considered technical challenges. For instance, in [10], the authors investigated the possibility of mitigating the intermittency of grid-connected PV systems through the installation of ESSs. Results showed that a properly sized battery system can alleviate network fluctuations.…”
Section: Related Workmentioning
confidence: 99%
“…The capacity of the TES and EES is a key factor to optimize CHP system operation and meet a given energy demand in an effective way, as well as the proper sizing and scheduling of storage systems heavily affect their application [61]. For this reason, a sensitivity analysis was performed on both the TES and EES capacities for the "independent energy systems" configuration, in order to evaluate the respective optimal size.…”
Section: Electrical and Thermal Energy Storagementioning
confidence: 99%